The effect of RF sputtering power variation on blocking layer TiO2 on the performance of DSSC - Alfiatul Ma'arifah; Nabella Sholeha; Herlin Pujiarti; Markus Diantoro; Arif Hidayat; Zurina Osman (Results in Surfaces and Interfaces)
In this study, optimization of the blocking layer (BL) TiO2 coating using radio frequency (RF) sputtering has been carried out to improve the performance of dye-sensitive solar cell (DSSC). The TiO2 blocking layer was created with variations in sputtering power (0, 140, and 180 W). Based on the results of x-ray diffraction (XRD) characterization, it shows that as the sputtering power increases, the crystal size decreases, thereby increasing the active surface area. The ultraviolet–visible (UV–Vis) results indicate that an increase in sputtering power can reduce the band gap from 3.83 eV to 4.04 eV. In this study, an increase in DSSC efficiency was obtained from 3.23% to 7.71%. This improvement in efficiency shows that the sputtered TiO2 blocking layer can reduce recombination, as evidenced by the increased electron lifetime. This is further supported by the electrochemical impedance spectroscoy (EIS) results, which show that the use of the sputtered TiO2 blocking layer increases the electron lifetime from 0.70 ms to 8.96 ms.